Duchenne muscular dystrophy caused by a deletion (c.5021del) in exon 35 of the DMD gene: A case report and review of the literature - Yue Liu; Yanhui Tang; Hui Zhang; Hongying Chen; Qing Luo; Jinbo Liu (Heliyon, 2024)
Duchenne muscular dystrophy (DMD MIM#310200) is a degenerative muscle disease caused by mutations in the dystrophin gene located on Xp21.2. The clinical features encompass muscle weakness and markedly elevated serum creatine kinase levels. An 8-year-old Chinese boy was diagnosed with Duchenne muscular dystrophy (DMD). Whole exome gene sequencing was conducted and the Sanger method was used to validate sequencing. A deletion (c.5021del) in exon 35 of the dystrophin gene was identified, which was predicted to generate a frameshift mutation and create an early termination codon (p.Leu1674CysfsTer47). It has a pathogenic effect against dystrophin in the muscle cell membrane of the patient. As such, prednisone treatment at a dose of 0.75 mg/kg.d was administered. After one month, a notable reduction in fall frequency was observed. Our new finding will expand the pathogenic mutation spectrum causing DMD.